2002
DOI: 10.1002/sia.1449
|View full text |Cite
|
Sign up to set email alerts
|

Surface studies of a chalcogenide glass ferric ion‐selective electrode Part 1: Influence of ferric and hydroxide ions on interfacial kinetics

Abstract: X-ray photoelectron spectroscopy (XPS), secondary ion mass spectrometry (SIMS),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…Clearly, this points to an elaborate nanostructural network of conductive filaments -highly conductive iron doped GeSe and Sb 2 Se 3 -that are able to impart a large effect on the bulk electrical conductivity of the membrane. Of course, the previous SEM research [44] had revealed a highly interwoven network of nanofilaments at concentrations of iron above 2 at%, and atomic force microscopy (AFM) for an Fe ISE exposed to 0.01 M Fe(NO 3 ) 3 revealed a nanoporous surface structure which arises from preferential oxidative attack of the crystalline phases that are less noble relative to the surrounding glassy matrix [22].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Clearly, this points to an elaborate nanostructural network of conductive filaments -highly conductive iron doped GeSe and Sb 2 Se 3 -that are able to impart a large effect on the bulk electrical conductivity of the membrane. Of course, the previous SEM research [44] had revealed a highly interwoven network of nanofilaments at concentrations of iron above 2 at%, and atomic force microscopy (AFM) for an Fe ISE exposed to 0.01 M Fe(NO 3 ) 3 revealed a nanoporous surface structure which arises from preferential oxidative attack of the crystalline phases that are less noble relative to the surrounding glassy matrix [22].…”
Section: Resultsmentioning
confidence: 98%
“…A reaction model, which is depicted by the cartoon in Figure 2, can be derived by reconciling the previously published data on the reactivity [33], response attributes [8,10,45] as well as SANS, SEM and AFM nanostructural information on the MSL [22,43,44] of the iron chalcogenide glass ISE. Initially, the iron doped nanocrystalline inclusions of GeSe and Sb 2 Se 3 (shown as white oval-like rods in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A further mechanistic study of the iron(III) chalcogenide glass ISE using secondary ion mass spectrometry (SIMS), EIS and XPS in various media [108,109] suggested that chloride, hydroxide, nitrate, etc. in seawater together with ubiquitous organic ligands do not pose a serious problem for the electroanalysis of Fe 3þ in seawater, but it is necessary to condition the electrode in seawater prior to analysis, while regular recalibration, reconditioning (preferably overnight) and frequent polishing is required, if the ISEs response in seawater is to remain internally consistent with its response in iron(III) calibration standards.…”
Section: Iron(iii) In Seawatermentioning
confidence: 99%
“…7 A recent EIS, XPS and SIMS study demonstrated that hydroxide accelerates dissolution of the chalcogenide glass via a corrosion mechanism. 8 Significantly, the formation of a mild passivation layer on the membrane surface has been shown to inhibit the charge transfer process. 8 …”
Section: Introductionmentioning
confidence: 99%
“…8 Significantly, the formation of a mild passivation layer on the membrane surface has been shown to inhibit the charge transfer process. 8 …”
Section: Introductionmentioning
confidence: 99%